Application of evolutionary techniques to temporal classification of cloud systems using satellite imagery - Parikh, Jo Ann; Daponte, John S; Vitale, Joseph N; Tselioudis, George (Proceedings of SPIE, 1998)
The objective of this research is to automate the classification of the temporal behavior of storm cloud systems based on measurements derived from consecutive satellite images. The motivation behind this study is to develop improved descriptions of cloud dynamics which can be used in general circulation models for prediction of global climate change. Analysis was applied to the International Satellite Cloud Climatology Project (ISCCP) low resolution cloud top pressure database for the first six days in April, 1989. A total of 296 midlatitude storm cloud components were tracked between consecutive 3-hour time frames. For each pair of components, temporal correspondence events were classified as either 1.) direct, 2.) merge, 3.) split, or 4.) reject. The reject class, which was used primarily to categorize pairs of unrelated systems, included storm cloud system dissipation and creation as well. Statistical, neural network, and evolutionary techniques were developed for finding solutions to the storm cloud correspondence problem. Evolutionary techniques applied to the problem consisted of 1.) a constraint-handling hybrid evolutionary technique and 2.) a genetic local search algorithm. The results demonstrate the potential of evolutionary techniques to yield meteorologically-feasible solutions, given appropriate constraints, to the two-frame storm tracking problem. © 1998 SPIE. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/042-405-237-322-980 tex.type: [object Object]
Keywords: Artificial intelligence; Climate change; Climate models; Cloud tracking; Correspondence problem; Correspondence problems; Evolutionary techniques; General circulation model; Genetic algorithms; Genetic local search algorithm; Global climate changes; Image classification; International satellite cloud climatology projects; Neural networks; Satellite imagery; Storms; Temporal classification; dept.csc